High definition i-SCAN endoscopy with water immersion technique accurately reflects histological severity of celiac disease - Iacucci, Marietta; Poon, Tiffany; Gui, X. Sean; Ghosh, Subrata (Endoscopy International Open, 2016)
Background and aims: Severe villous atrophy can be revealed with conventional white light endoscopy (WLE), however, milder grades or patchy villous atrophy are more difficult to detect. Novel endoscopic techniques such as high definition i-SCAN endoscopy with the water immersion technique (i-SCAN-HDWI) may provide the ability to visualize duodenal villi more accurately. We aimed to determine the performance of i-SCAN-HDWI in evaluating the severity of histological damage in the duodenum of patients with celiac disease.Patients and methods: A retrospective cohort study was performed in a single tertiary academic endoscopic center. We studied 58 patients (46 women; median age 36.5 years, range 18 – 72 years) with positive anti-TTG IgA antibody. The villous pattern of the second part of the duodenum was assessed by WLE and i-SCAN-HDWI. The endoscopic grades in both techniques were correlated using Marsh histologic grades by Spearman correlation coefficient. The diagnostic accuracy of i-SCAN-HDWI for detection of patchy or complete atrophy of the villi was evaluated.Results: A significant correlation was demonstrated between endoscopic grade using i-SCAN-HDWI and Marsh histologic grade (r = 0.732; P < 0.00001). The correlation between WLE grade and Marsh histologic grade was inferior to i-SCAN-HDWI (r = 0.31; P = 0.01). The sensitivity of i-SCAN-HDWI was 96 % (95 %CI: 85 – 99 %) and the specificity was 63 % (95 %CI: 26 – 90 %) in diagnosing abnormal biopsy consistent with celiac disease.Conclusion: i-SCAN-HDWI endoscopy can reflect the histological severity of celiac disease more accurately than conventional WLE alone. This novel endoscopic imaging can improve the diagnostic yield of duodenal biopsies in celiac patients, especially for those with a patchy distribution of villous damage.